Determining Media Ethics in Traditional Media: Terminological Issues - Donev, Dejan (Hrvatsko filozofsko društvo, 2017)
In traditional media we will often find a wrongful persuasion lingering through: that media ethics is synonymous with journalism ethics, that is, that we can place a sign of equivalence among these two ethics. This misinterpretation consists in narrowing down the relevant moral-ethical media communications and media practice solely to the journalist’s field, instead of understanding it as the application of the philosophical-ethical thinking of the specific area of human practice related to the mass communication. This indicates tendency to reject the fact that the moral-ethical responsibility may be divided in every mass-media act accordingly. Thus it is simpler to consider that the media ethics is not that much more different and diverse than the journalism ethics. Because of that, the first step we ought to do is to terminologically distinguish the notion and the subject matter of media ethics from the notion and subject matter of journalism ethics.
Déterminer l’éthique des médias dans les médias traditionnels : difficultés terminologiques
Bestimmung der Ethik der Medien in traditionellen Medien: terminologische Schwierigkeiten
Keywords: media, ethics, professional moral, journalism, mass communication, communication means